6x² + 6/x² + 5x + 5/x - 38 = 0
6(x² + 1/x²) + 5(1/x + x) - 38 = 0
x ≠ 0
замена
1/x + x = t
(1/x + x)² = t²
1/x² + 2*1/x * x + x² = t²
1/x² + 2 + x² = t²
1/x² + x² = t² - 2
6(x² + 1/x²) + 5(1/x + x) - 38 = 0
6(t² - 2) + 5t - 38 = 0
6t² - 12 + 5t - 38 = 0
6t² + 5t - 50 = 0
D = 25 + 4*50*6 = 1225 = 35²
t12 = (-5 +- 35)/12 = 30/12 (5/2) - 40/12 (-10/3)
обратно к х
1. 1/x + x = 5/2
2x² - 5x + 2 = 0
D = 25 - 16 = 9 = 3²
x12 = (5 +- 3)/4 = 2 1/2
2. 1/x + x = -10/3
3x² + 10x + 3 = 0
D = 100 - 36 = 64 = 8²
x12 = (-10 +- 8)/6 = -3 -1/3
ответ x = {2,1/2,-3,-1/3}
вкратце
1. −(a+b)−(c−d)−(e−f)=−a-b−c+d−e+f
2. (8ab+3b)−(6ab−3b)+4a=8ab+3b−6ab+3b+4a=2ab+6b+4а
если a=6 и b=3. 2*6*3+6*3+4*6=36+18+24=78
3. 0,2x²+0,04y² +0,16x²−0,07y²=0,36x²-0,03y²
(0,2x²+0,04y²) -(0,16x²−0,07y²)=0,2x²+0,04y²-0,16x²+0,07y=0.11у²+0.04х²
4. (9a−13b+29c)−(−24a+29b−24c) =9a−13b+29c+24a-29b+24c=33а-42b+53с
5. (637d−214d²)+(114d²−137d)= 637d−214d²+114d²−137d=500d-100d²
6. 16−(7h+5)+4= 16−7h-5+4=15−7h
7. (x²−4x+3)−(3x−2x²+4)=x²−4x+3−3x+2x²-4=3х²-7х-1; если x=2.
3х²-7х-1=3*2²-7*2-1=12-14-1=-3
8. x³+3x²−x+4x³+2x²−x +5x²−3x³+4x =2x³+10x²+2х
9. это 42, т.к. 42-24=18